(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article examines the problem of developing the professional readiness of preschool education teachers in Uzbekistan, with special attention paid to key aspects related to the development of personnel in the country’s preschool education sector.